Supporting the inclusion of young children in childcare settings through professional development: perceptions of educators and managers - Dionne, Carmen; Paquet, Annie; Lemire, Colombe; Dugas, Claude; Londono, Maria; Dubé, Annie-Claude (Frontiers in Education, 2025)
BackgroundInclusion in early childhood contributes to building equitable and diverse educational settings, fostering societal acceptance to differences. Nevertheless, obstacles remain to implementing inclusive practices from an early age. Professional development, particularly through coaching, is seen as a factor facilitating quality early childhood education practices. As part of an action-research project, therefore, this study aims to document the perceptions of educators and managers after 1 year of professional development based on the use of a curriculum-based assessment and embedded intervention/instruction in inclusive childcare settings.MethodThis article describes a qualitative study aimed at documenting the perceptions of educators and managers as regards changes perceived following the professional development received. The perceptions of 14 educators and 6 managers are analyzed using semi-structured interviews.ResultsResults suggest that professional development helps support quality inclusive educational practices. Participants address certain aspects of their educational practices, such as observation and intervention planning, to fine-tune the learning opportunities offered consistent with children’s development. They report that coaching is an opportunity to examine their practice, which fosters their sense of competence. Results also underline the importance of the leadership role of childcare managers in supporting educational staff.DiscussionThe perceptions of educators and managers highlight the value of coaching in supporting educational practices in inclusive childcare settings. Improved individualization of educational practices based on the developmental needs of each and every child enhances environments’ capacity for quality intervention for all children.